Actual practices of community pharmacists in the management of diabetes: a comparison of simulated patient-based study with perceived role of involvement - Ashenafi Kibret Sendekie; Amensisa Hailu Tesfaye; Yabibal Berie Tadesse; Abera Dessie Dagnaw; Eyayaw Ashete Belachew (Taylor & Francis Group, 2024)
ABSTRACTObjectives: This study evaluated the level of community pharmacy professionals' (CPPs) actual practices and contrasted it with their self-reported perceived involvement in diabetes management.Methods: A self-reported cross-sectional and simulated patient (SP)-based study were employed at community drug retail outlets (CDROs) in Northwest Ethiopia. SP-case scenarios were used to examine the actual practices of CPPs in diabetes management and were compared with self-reported perceived involvement. The data were managed and analysed using SPSS version 26.Results: About 184 participants in the self-reported and 100 CPPs' actual practices using three SP visits were included. The overall actual practice (17.8%) was found to be significantly different compared with the perceived level of involvement (73.5%) (p-value <0.05). About 94.3% of CPPs dispensed requested medications to the SP without a prescription. Despite most participants being perceived to be involved, more than 76% of CPPs did not counsel the SP for lifestyle modifications, avoiding risky behaviours, adherence to treatment, routine blood glucose checkups, diabetic foot care techniques, or consultation with physicians for further management.Conclusion: A significant discrepancy between actual practices and perceived CPPs' involvement in the management of diabetes was observed. The findings may suggest that exploring possible gaps may be crucial.